Generating functions for the Clebsch–Gordan coefficients. (8th February 2016) - Bergeron, Geoffroy; Vinet, Luc
Abstract: Generating functions for Clebsch–Gordan coefficients of are derived. These coefficients are expressed as limits of the dual q -Hahn polynomials. The generating functions are obtained using two different approaches respectively based on the coherent-state representation and the position representation of